ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN (Studi Empiris Perusahaan Manufaktur yang listing di Bursa Efek Indonesia Periode 2008 – 2010) - Hardiatmo, Budi; Daljono, Daljono (Diponegoro Journal of Accounting, 2013)
This research was performed to examine the effect of variable profitability, liquidity, leverage, growth firms and firm size on dividend policy by manufacturing companies listed on the Stock Exchange of Indonesia from 2008 to 2010. The variable profitability as measured by ROA, liquidity as measured by CR, leverage as measured by DER, growing company as measured by sales growth, firm size measured with the natural log of total assets and dividend policy with the House. The population of this research is 142 manufacturing companies listed on the Stock Exchange of Indonesia from 2008 to 2010. The sampling technique used was purposive sampling criteria: (1) manufacturing companies listed on the Stock Exchange the period 2008 to 2010, (2) companies that have dividend period from 2008 to 2009, and (3) the company has a complete financial statement data from 2008 to 2010 . Data obtained from the publication ICMD 2010 and official website BEI (www.idx.co.id). Obtained a sample of 22 companies. The analysis technique used is multiple regression. The results of multiple regression analysis demonstrated that simultaneous influence of profitability, liquidity, leverage, growth and firm size on dividend policy has a significant effect. Effect of partial significant positive effect on the profitability of dividend policy, liquidity and leverage not significant negative effect on dividend policy, corporate growth is not significant positive effect on dividend policy and firm size has a significant negative relationship dividend policy.